Evaluasi Distribusi Dokter dan Akses Masyarakat Terhadap Pelayanan Medis di Kabupaten Gunungkidul Tahun 2010 - Abdul Azis; Andreasta Meliala; Lutfan Lazuardi (Center for Health Policy and Management, 2012)
Background. The lack number of medical provider and imbalanced distribution are the most relevant issues in human resource planning and manning which effected on the decreasing of health service indicator as the impact of lack of skillful and experienced manpower when the health service demand keeps increasing. Hence, evaluation on availability and distribution of medical service as a basic to create a policy on medical service arrangement in Gunungkidul district is necessary. Objective. This research was aimed to identify the availability and distribution on medical service as well community access in Gunungkidul district. Method. This was a case study research that was conducted in Gunungkidul district in February – April 2010 in Healh Office, Regional Employee Board, 3 government hospitals, 30 Primary Health Care and 111 branch Primary Health Care, 46 clinics and 51 private doctors. The data was collected from secondary data in 2008-2010 and in depth interview toward government authority who managed medical providers; 6 in health office, 3 in Regional Employee Board, 30 doctors and 30 medical service users. In addition, the data was analysed descriptively. Result. There was a lack of the availability of medical officer in Gunungkidul district which was caused that there were many employees who resigned from the job than those who was signed in the past 3 years including private medical officers who were depends on the role of government health officer who had double practice. The arranged policy was not yet maximum because of the limited funding. The distribution of medical service was more in the area with high Product Domestic Regional Bruto and in municipalities. The distance to get medical service is in medium category. There was medical service unavailability from 9 PM up to 5 AM in urban areas except in the sub district which had inpatient treatment in Primary Health Care and in municipality. Conclusion. There was a lack of availability of medical provider in Gunungkidul district. The arranged policy was not yet optimum because of the limited funding. Distribution of medical service was more in the area with high Product Domestic Regional Bruto and municipality with medium category community access and there was still medical service unavailability at night.Latar Belakang. Jumlah tenaga medis yang kurang dan distribusi yang belum merata merupakan isu-isu paling relevan dalam human resource planning dan suplai tenaga yang berdampak pada indikator pelayanan kesehatan yang menurun akibat kekurangan tenaga terampil dan berpengalaman pada saat permintaan pelayanan terus meningkat. Sehingga perlu dilakukan kajian sebagai dasar menetapkan kebijakan di Kabupaten Gunungkidul. Tujuan Penelitian. Mengidentifikasi ketersediaan dan distribusi pelayanan medis serta akses masyarakat di kabupaten Gunungkidul. Metode Penelitian. Penelitian studi kasus ini dilakukan di Kabupaten Gunungkidul pada bulan Februari -April 2010 di Dinas Kesehatan, Badan Kepegawaian Daerah, 3 rumah sakit, 30 Puskesmas dan 111 Pustu, 46 Klinik/ BP/ RB dan 51 Dokter praktek swasta. Data dikumpulkan dari data skunder tahun 2008 - 2010 dan wawancara mendalam kepada pejabat pengelola tenaga medis. 6 pejabat dinas kesehatan, 3 di Badan Kepegawaian Daerah, 30 dokter dan 30 masyarakat. Analisis data secara deskriptif. Hasil Penelitian : Ketersediaan tenaga medis Kabupaten Gunungkidul masih kurang di sebabkan dalam 3 tahun terakhir jumlah yang keluar lebih banyak di bandingkan dengan yang masuk, termasuk tenaga medis swasta yang ketersediaannya tergantung dari tenaga medis pemerintah yang praktek ganda. Kebijakan yang di susun belum optimal karena terbatasnya pembiayaan.Pola distribusi pelayanan medis menumpuk di wilayah dengan PDRB tinggi, perkotaan dan mudah transportasinya. Jarak pelayanan untuk di akses masyarakat dengan kategori mudah. Tetapi terjadi kekosongan pelayanan medis pada malam hari di pedesaan Kesimpulan. Ketersediaan tenaga medis Kabupaten Gunungkidul masih kurang. Pola distribusi pelayanan medis lebih banyak di wilayah perkotaan, PDRB tinggi dan transportasi yang mudah. Sedangkan akses masyarakat terhadap pelayanan mudah tetapi terjadi kekosongan pelayanan medis pada malam hari di pedesaan. Kebijakan yang ada belum optimal karena terbatasnya biaya, daerah miskin, pedesaan, sulit transportasi/ komunikasi.